Encyclical "Veritatis Splendor": perspectives for Medicai Ethics - Carrasco de Paula, Ignazio (Medicina e Morale, 1994)
This article highlights the double relationship between the encyclical Veritatis Splendor and Medicai Ethics. First of alI, the recent pontificai document aims to overcome some erroneous interpretations (primarily consequentialism and proportionalism) of catholic morality which "calculate" moral good and evil according to the consequences or proportion between the good and bad effects of human behavior. It is not coincidental that these hypotheses, which use parameters similar to the utilitaristic "cost-benefit" model, are partially motivated by the attempt to solve problems raised in the field of Bioethics. Secondly, the encyclical reaffirms the fundamental concepts of christian ethics: the relationships between law and freedom, conscience and truth, and morals and faith. The encyclical designs the theoretical bases for Bioethics worthy of human dignity: the link between metaphysics and anthropology, the recognition of the natural law as the rational normative criterion for all, and the overcoming of the relativism inherent to ethics of consent or of subjective interests through an understanding of the role of moral absolutes and the centrality of the dignity of the person. Medicai Ethics, which aim to promote the good of the patient, must assure that this good corresponds to the person, or else it will not lead to true, moral progress.